The History of Musical Instruments - Sachs, Curt 1881-1959 (New York Norton, 1940)
Written by one of the world's most distinguished musicologists, this is the first comprehensive history of musical instruments. It traces their evolution from prehistoric to modern times, combining scholarship with insight in a remarkable fusion of music, anthropology, and the fine arts. Includes 24 plates and 167 illustrations.
Keywords: Past; Organology